Governança de TI na UFSM: guia de apoio à implementação de processos ITIL na gestão de serviços de TI - Vianna, Paulo Henrique (2023)
The present work proposes the implementation of an IT service management process in a federal educational institution. Initially, a survey was carried out on the degree of use of tools from IT Governance in the Data Processing Center (CPD) of the University Federal of Santa Maria (UFSM) with an emphasis on IT service management tools, after this verification, possible processes offered by the ITIL IT Governance framework that could collaborate with the management of these types of services were listed, finally the process was selected service level management and with this the process was implemented in the OTRS system in a test environment. The research was based on a goal presented in the UFSM PDTI for the years 2021-2024, this goal foresees the implementation of processes originating from ITIL for IT service management. To this end, this work is characterized as research with a qualitative and descriptive approach, which, after analyzing the data collected through direct observation, interviews and documentary analysis, made it possible to develop a guide that describes the steps for implementing the process. service level management in an environment that simulates the resources currently used by the CPD. The guide can be used by the CPD to guide the possible inclusion of the process in its environment and also serve as an information base for similar institutions that wish to apply validated methodologies for Information Technology Management in their IT service management processes.